Information and analytical technologies in trading enterprise management - O. Klepikova; J. Danylchuk; T. Zagray (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка, 2021)
The article considers economic and mathematical methods and information technologies for managing the processes of trade enterprise. Economic and mathematical models for solving warehousing logistics problems, stochastic and statistical models of inventory management, models of optimal management and queuing systems are analyzed. Flexible tools are used to increase the efficiency of trade enterprise management and timely decision-making. The tools combine the use of mathematical models, a simulation model and information-analytical technologies. The study was carried out in three stages. The simulation model is designed in the software iThink. The simulation model was used to forecast sales, incomes, expenses and profit, processes of goods purchases, which take into account the factors of seasonality and the rest of production both in a warehouse and in the enterprise as a whole. The efficiency indicators of the enterprise are calculated and the possibility of payroll depending on income and dividends to owners is analyzed. An investment project has been designed in the software «Alt-Invest». This project analyzes the possibility of opening a new store with regard for financial activities, the development of a business plan for an investment project, the preparation of financial feasibility study, and the assessment of the impact of external factors and internal parameters on the overall effectiveness of the project. A comparative assessment is carried out in order to select the most promising project option. ABC-XYZ scenario was designed in the software platform Loginom. Using this analysis, the product range was divided into groups depending on the revenue and financial capabilities of the enterprise.